Aligning the binder effect on sodium–air batteries. Issue 4 (11th January 2018) - Sun, Qian; Lin, Xiaoting; Yadegari, Hossein; Xiao, Wei; Zhao, Yang; Adair, Keegan R.; Li, Ruying; Sun, Xueliang
Abstract : Polymer binders are revealed to dominatingly impact the electrochemical behavior and side reactions/products of sodium-air batteries. Abstract : Sodium–air batteries are attracting increasing research interest due to their high theoretical energy density and environmentally benign characteristics. Although sodium–air batteries share a similar concept, design, and composition when compared with their lithium–air counterparts, they still show many differences in their electrochemical behaviors and mechanisms. In the present work, the employment of four different types of polymers as binders in air electrodes for sodium–air batteries is presented, while the electrochemical and physical characterizations are carried out. Insights into how polymer binders impact the reaction mechanisms and formation of superoxide/peroxide species of sodium–air batteries from the view of their functional groups are revealed.